2012
DOI: 10.1093/jxb/ers348
|View full text |Cite
|
Sign up to set email alerts
|

The form of nitrogen nutrition affects resistance against Pseudomonas syringae pv. phaseolicola in tobacco

Abstract: Different forms of nitrogen (N) fertilizer affect disease development; however, this study investigated the effects of N forms on the hypersensitivity response (HR)—a pathogen-elicited cell death linked to resistance. HR-eliciting Pseudomonas syringae pv. phaseolicola was infiltrated into leaves of tobacco fed with either or . The speed of cell death was faster in -fed compared with -fed plants, which correlated, respectively, with increased and decreased resistance. Nitric oxide (NO) can be generated by nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
128
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(142 citation statements)
references
References 87 publications
11
128
0
3
Order By: Relevance
“…For instance, symptoms of black root rot (Rhizoctonia solani) of sugar beets (Afanasiev and Carlson, 1942) or Fusarium wilt on tomato (Borrero et al, 2012) were reported to increase following NH þ 4 nutrition. In a recent metabolomic study, we have found that NH þ 4 nutrition enhances the content of apoplastic sugar and amino acids as well as GABA, thereby increasing the availability of nutrients to the invading pathogen; in this case P. syringae (Gupta et al, 2013). Conversely, under NO -3 nutrition, increased resistance to P. syringae was observed.…”
Section: Direct Contributions By N To Defensive Metabolitesmentioning
confidence: 88%
See 3 more Smart Citations
“…For instance, symptoms of black root rot (Rhizoctonia solani) of sugar beets (Afanasiev and Carlson, 1942) or Fusarium wilt on tomato (Borrero et al, 2012) were reported to increase following NH þ 4 nutrition. In a recent metabolomic study, we have found that NH þ 4 nutrition enhances the content of apoplastic sugar and amino acids as well as GABA, thereby increasing the availability of nutrients to the invading pathogen; in this case P. syringae (Gupta et al, 2013). Conversely, under NO -3 nutrition, increased resistance to P. syringae was observed.…”
Section: Direct Contributions By N To Defensive Metabolitesmentioning
confidence: 88%
“…One was the increase in polyamine levels, i.e. putrescine, spermidine and spermine production (Gupta et al, 2013). Polyamines are known to increase plant resistance; for example, increasing in barley (Hordeum vulgare) during the hypersensitive response (HR)-associated resistance response against the powdery mildew fungus B. graminis f. sp.…”
Section: Direct Contributions By N To Defensive Metabolitesmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, compared to the NH 4 + , NO 3 − increased tobacco resistance to Pseudomonas syringae pv. p haseolicola by the accumulation of SA and NO, as well as the increase in polyamine-mediated HR-linked defence [41]. In addition, studies have reported that a high N supply generally increases the susceptibility of plants to obligate parasites but decreases the susceptibility of plants to necrotrophs and facultative parasites [19,35].…”
Section: Discussionmentioning
confidence: 99%